STRATEGI PENGEMBANGAN PRIVATE LABEL DALAM BISNIS RITEL - MULYONO, PATRISIA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Changes in an uncertain business environment, realize the business establish appropriate retail strategy to achieve corporate objectives. Private Brand is one of the strategies used by retailers today to compete among other retailers and retain customers. Private brand is a brand owned by the retailer. Where retailers have products with the brand of the retailer itself. Brand is one of the factors that influence consumer purchasing decisions so that retailers should be able to do private brand development strategy appropriately. Retailers need to be more creative and innovative in developing private brand to attract customers and differentiate their products from the competition. So from the uniqueness of the private brand different from competitors can lead to customer loyalty in the retailer. The existence of private brand products retailer may increase the variety of products offered to consumers. Private brand development strategy in the retail business to see that retailers should be able to consider the use of the private brand. Retailers also need to develop a branding strategy and pricing strategy private private brand because the brand is one of the factors influence the purchase decisions of consumers and the retail market development in Indonesia, Indonesian consumers are price-sensitive market potential for the development of the brand. So it can be seen that the private brand has a bright prospect.